Graded refraction index antireflection coatings based on silicon and titanium oxides - Abdelhakim Mahdjoub (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
Thin films with a graded refraction index constituted from silicon and titanium oxides were deposited by plasma enhanced chemical vapor deposition using electron cyclotron resonance. A plasma of oxygen reacted with two precursors: the tetraethoxysilane (TEOS) and the titanium isopropoxide (TIPT). The automatic regulation of the precursor flows makes it possible to modify the chemical composition, and consequently the optical index, through the deposited films. To control the thickness, the refraction index and the growth kinetics, in situ spectroscopic ellipsometer was adapted to the reactor. The analysis of ex situ ellipsometric spectra measured at the end of each deposition allow to determine a refraction index profile and optical properties of the inhomogeneous deposited films. Measurements of reflectivity carried out in the ultraviolet-visible-near infrared range show that these films could be used as antireflective coatings for silicon solar cells: 3.7 % weighted average reflectivity between 300 and 1100 nm and 48 % improvement of the photo-generated current were obtained.